Amplified electrochemical genotyping of single-nucleotide polymorphisms using a graphene–gold nanoparticles modified glassy carbon platform1. Issue 37 (25th April 2015) - Khoshfetrat, Seyyed Mehdi; Mehrgardi, Masoud A.
<x xml:space="preserve">Abstract</x> A triple signal amplification strategy for the single nucleotide polymorphisms (SNPs) genotyping is reported using the graphene–gold nanoparticles (GR–AuNPs) as a sensitive platform and monobase-modified silver and gold nanoparticles (M-NPs).